1998
DOI: 10.1146/annurev.biochem.67.1.425
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin System

Abstract: The selective degradation of many short-lived proteins in eukaryotic cells is carried out by the ubiquitin system. In this pathway, proteins are targeted for degradation by covalent ligation to ubiquitin, a highly conserved small protein.Ubiquitin-mediated degradation of regulatory proteins plays important roles in the control of numerous processes, including cell-cycle progression, signal transduction, transcriptional regulation, receptor down-regulation, and endocytosis. The ubiquitin system has been implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
5,338
2
63

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 7,729 publications
(5,439 citation statements)
references
References 302 publications
(323 reference statements)
36
5,338
2
63
Order By: Relevance
“…At least four ubiquitin molecules, conserved peptides of 76 amino acids, are required for a poly-ubiquitin chain to be recognized by the proteasome. Hershko and colleagues in the early 1980s showed that poly-ubiquitylation requires three ATP-dependent enzymes: the ubiquitin activation enzyme (E1), a family of ubiquitin conjugating enzymes (E2) and a family of ubiquitin protein ligases (E3) ( Hershko & Ciechanover, 1998). First, ATP hydrolysis is required to activate the AMP linkage to the C-terminal glycine of ubiquitin which enables the transfer of the ubiquitin moiety to the active site cysteine of the E1.…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…At least four ubiquitin molecules, conserved peptides of 76 amino acids, are required for a poly-ubiquitin chain to be recognized by the proteasome. Hershko and colleagues in the early 1980s showed that poly-ubiquitylation requires three ATP-dependent enzymes: the ubiquitin activation enzyme (E1), a family of ubiquitin conjugating enzymes (E2) and a family of ubiquitin protein ligases (E3) ( Hershko & Ciechanover, 1998). First, ATP hydrolysis is required to activate the AMP linkage to the C-terminal glycine of ubiquitin which enables the transfer of the ubiquitin moiety to the active site cysteine of the E1.…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
“…In eukaryotic cells two highly conserved degradation pathways exist: long-lived proteins are degraded within the lysosome, an organelle with membranes which protect the surrounding cytoplasm against lysosomal hydrolases ( Rendueles & Wolf, 1988); short-lived proteins are degraded by proteasomes, multimeric protease complexes which move between the nucleo- and cytoplasm ( Hershko & Ciechanover, 1998). Proteasomal substrates are often nuclear proteins such as proteins regulating cell cycle progression (cyclin-dependant kinases and their inhibitors), gene expression (transcriptions factors), DNA damage and stress response; although, misfolded proteins occurring during protein synthesis in the cytoplasm are also rapidly degraded by the proteasome ( Kirschner, 1999; Vabulas & Hartl, 2005; von Mikecz, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiqutination recruits a catalytic reaction to ubiquitinate the substrate 1. Three ubiquitin enzymes, E1 ubiquitin activating, E2 ubiquitin conjugating, and E3 ubiquitin ligase are sequentially recruited in this cascade reaction 2, 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…One major pathway is the regulation of protein amount through ubiquitin-dependent proteolysis (Pagano, 1997;Hershko, 1997;Hershko and Chiechanover, 1998;Almond and Cohen, 2002). The ubiquitin-dependent proteolysis system requires a set of enzymes as follows: ubiquitin-activating enzyme (E1), ubiquitin-conjugating enzyme (E2) and ubiquitin ligase (E3).…”
Section: Introductionmentioning
confidence: 99%